Pengaruh Perlindungan Saksi dan Korban Terhadap Keberanian Masyarakat Melapor Tindak Pidana Kekerasan Berat - Putri Ramadhani Rangkuti; Melia Dwi Hasanah; Nazwa Bunga Rezki Perdana Lubis; Nadia Putri Naya; Rizka Arifah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Protection for witnesses and victims is a crucial component of the criminal justice system, particularly in cases involving serious violent crimes that often cause trauma, fear, and potential threats to those who report them. This study aims to analyze the influence of witness and victim protection on the willingness of the public to report serious acts of violence. Using a socio-legal approach, the study examines relevant legislation, empirical data, and supporting literature. The findings indicate that public willingness to report crimes is strongly affected by the availability of physical security, confidentiality of identity, legal assistance, and psychological support. Inadequate, inaccessible, or unresponsive protection mechanisms tend to reduce the courage of individuals to disclose incidents. Conversely, comprehensive and well-implemented protection measures enhance public participation, facilitate law enforcement processes, and strengthen the prevention of serious violent crimes. These results highlight the importance of optimizing witness and victim protection institutions through improved coordination, adequate resources, and broader public outreach so that individuals feel safe and confident when reporting criminal acts.